Ground Motion Model for Small-to-Moderate Earthquakes in Texas, Oklahoma, and Kansas. Issue 1 (February 2019) - Zalachoris, Georgios; Rathje, Ellen M.
A ground motion model (GMM) tuned to the characteristics of the observed, and potentially induced, seismicity in Texas, Oklahoma, and Kansas is developed using a database of 4, 528 ground motions recorded during 376 events of Mw > 3.0 in the region. The GMM is derived using the referenced empirical approach with an existing Central and Eastern North America model as the reference GMM and is applicable for Mw = 3.0–5.8 and hypocentral distances less than 500 km. The proposed model incorporates weaker magnitude scaling than the reference GMM for periods less than about 1.0 s, resulting in smaller predicted ground motions at larger magnitudes. The proposed model predicts larger response spectral accelerations at short hypocentral distances (≤20 km), which is likely because of the shallow hypocenters of events in Texas, Oklahoma, and Kansas. Finally, the VS 30 scaling for the newly developed model predicts less amplification at VS 30 < 600 m/s than the reference GMM, which is likely because of the generally thinner sediments in the study area. This finding is consistent with recent studies regarding site amplification in Central and Eastern North America.